Enhancing Masonry Structures: Textile Reinforcement and Sustainable Materials for Seismic Retrofitting (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Masonry structures are commonly preferred in many countries for low-rise buildings due to their advantages, including easy and rapid construction, abundant building materials, and the absence of the need for specialized techniques. These structures exhibit considerable strength, enabling them to withstand significant compressive stress. However, their limited ductility makes them susceptible to damage during dynamic loading events such as earthquakes. Unreinforced masonry (URM) structures, found in numerous historical buildings worldwide, require seismic retrofitting. Strengthening techniques like ferro-cement jacketing, textile reinforcement mortar, and fibre-reinforced polymer sheets have been employed. Among these methods, textile reinforcement mortar has proven effective in enhancing the shear strength of URM walls while minimally impacting their cross-sectional area and weight. This technique improves the shear capacity of bricks and enhances the bonding strength between adjacent bricks. In this study, polypropylene fibre mats are utilized as textile reinforcement mortar, placed between two layers of mortar connecting two adjacent bricks. Concrete and mortar, with cement and sand as integral components, are essential and versatile building materials widely used in construction. However, cement production is environmentally unfriendly, relying on lime obtained through mining, depleting limited lime sources and causing destruction to natural landscapes. Furthermore, the production of one kilogram of cement emits an equivalent amount of harmful carbon dioxide. The demand for natural sand is also increasing due to extensive development projects. Thus, the search for alternative binding and filling materials to replace cement and sand is significant from economic and environmental perspectives. In this research, cement is partially substituted with silica fume up to 40%, and sand is partially replaced with pond ash up to 20% by weight, individually or in combination. Two cement mortar ratios, 1:4 and 1:6, are considered, resulting in nine different mixes under each ratio. Two types of brick materials, fly ash bricks and AAC bricks, are compared regarding their physical and mechanical properties, along with the properties of their respective masonry mortars.